Lei da Escuta Protegida, n° 13.431/17: reflexões sobre a proteção e garantia dos direitos de crianças e adolescentes vítimas ou testemunhas de violência - Cecílio, João Maurício Lago (Brasil, 2025)
This article aims to present a theoretical debate on the Protected Listening Law, No. 13,431/17, between the institutions that make up the System for Guaranteeing the Rights of Children and Adolescents. This law is an important instrument for protecting and guaranteeing the human rights of children and adolescents who have had their rights violated. The Brazilian Federal Constitution, through the important contribution of article 227 and the Child and Adolescent Statute, law 8069/90, together with other legislation, aim to guarantee the protection of this segment of the population. The need to discuss Law 13. 431, of April 4, 2017, arose from reflection on existing standards to act as an intervention mechanism on revictimization and the role of the Protection Network in supporting children and adolescents, in order to minimize the impacts of the violence suffered. A bibliographical research was carried out for the theoretical debate and reflections carried out in this article.